POLA KOMUNIKASI INDIGO DENGAN LINGKUNGAN SEKITAR - Sukoco, Baktyar Ersat (Jurnal Insani, 2015)
This research is motivated by the problems of discrimination and stigma that still haunt a person with special psychological researchers in this discussion takes the theme of an indigo, where the phenomenon is still rare and became part of the minority that naturally would feel pressured by the majority. A wide range of both positive and negative attitudes that occur around the indigo and communication patterns to an indigo surroundings become the subject of this research involves the concept of self an indigo with two speakers and the perception of the surrounding environment.Purpose of this study is to investigate and deepen the communication patterns of a different indigo with someone in general in terms of communication and social interaction. This study uses qualitative research methods to jump directly to the field observation, interviews and documentation. Subjects were Indrad 28 years old in Surabaya and Dian Ayu 28 years old in Jakarta. This research has been started since the year 2013 until the observation of this study was made. The results of the study there are two sources, first indigo Indrad has communication patterns tend to be closed and a loner, more get the behavior of discrimination by people around. And both indigo Dian communication patterns that tend to open and expressive, many people enjoy around, minimal diskrimiasi behavior.